Acoustic deterrent devices as mitigation tool to prevent dolphin-fishery interactions in the Aeolian Archipelago (Southern Tyrrhenian Sea, Italy) - BRUNO, CHIARA ANASTASIA; CASERTA, VALENTINA; SALZERI, PERLA; BONANNO FERRARO, GIUSY; PECORARO, FEDERICO; LUCCHETTI, ALESSANDRO; BOITANI, LUIGI; BLASI, MONICA FRANCESCA (Mediterranean Marine Science, 2021)
In this study, acoustic deterrent devices (Pingers) have been tested to reduce dolphin-fishery interaction in the Aeolian Archipelago (Southern Italy), where ecosystem degradation and overfishing have increasingly brought bottlenose dolphin (Tursiops truncatus) and striped dolphin (Stenella coeruleoalba) into conflict with local artisanal fishery. Thirty-six trials with FishTek banana Pingers have been performed between April and September 2017 on Spicara maena gillnet, trammel net, “Lampara” net, and hand-operated squid jig line (“Totanara”). A conspicuous decrease in depredation-related damages was recorded on S. maena gillnet (100 %) and Lampara net (86 %) tests, corresponding to a great increase in catch weight (Kg) and profit (€). On the contrary, in squid hand-jig lines, the depredation events were high (60 %) and a dramatic decrease of catch and profit was recorded. No significative differences in weight and profit and any dolphin-related damages have been observed between test and control trammel nets, but fish species included in dolphin diet were more abundant in test than in control nets. Our results suggested that different factors, such as dolphin species, season, habitat and fish species distribution, may affect the efficacy of Pingers. Furthermore, discard represent about 49 % of total catch and include potentially valuable bycaught (namely non-target) fish species, such as Sparisoma cretense, highly abundant in the area but poorly evaluated on the local market. Pingers and inclusion of non-target species in the local market represent potential mitigation tools to reduce the conflict, but they need adequate planning.